2014
DOI: 10.1128/aem.00323-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Self-Assembly of Stable Green Fluorescent Protein Fusion Particles and Their Uses in Enzyme Immobilization

Abstract: Bacterial inclusion bodies are aggregations of mostly inactive and misfolded proteins. However, previously the in vivo self-assembly of green fluorescent protein (GFP) fusions into fluorescent particles which displayed specific binding sites suitable for applications in bioseparation and diagnostics was demonstrated. Here, the suitability of GFP particles for enzyme immobilization was assessed. The enzymes tested were a thermostable ␣-amylase from Bacillus licheniformis, N-acetyl-D-neuraminic acid aldolase (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Previous studies have developed a mutated version of GFP, termed split-GFP or self-assembly GFP, where the gene encoding the first 10 beta sheets (GFP1-10) and the gene encoding the last beta sheet (GFP11) are expressed separately but are able to self-assemble and fluoresce (Cabantous et al, 2005;Cabantous and Waldo, 2006). Selfassembly GFP has been previously reported to enhance protein solubility, reduce formation of bacterial inclusion bodies and for the immobilization of various enzymes in recombinant E. coli BL21 (DE3) (Cabantous and Waldo, 2006;Venning-Slater et al, 2014). It has also been applied for topology analyses of membrane-bound enzymes in N. benthamiana, without affecting their biological functionality (Xie et al, 2017).…”
Section: Synthetic Design Of An Elongase Expression Cassette Using Rbmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have developed a mutated version of GFP, termed split-GFP or self-assembly GFP, where the gene encoding the first 10 beta sheets (GFP1-10) and the gene encoding the last beta sheet (GFP11) are expressed separately but are able to self-assemble and fluoresce (Cabantous et al, 2005;Cabantous and Waldo, 2006). Selfassembly GFP has been previously reported to enhance protein solubility, reduce formation of bacterial inclusion bodies and for the immobilization of various enzymes in recombinant E. coli BL21 (DE3) (Cabantous and Waldo, 2006;Venning-Slater et al, 2014). It has also been applied for topology analyses of membrane-bound enzymes in N. benthamiana, without affecting their biological functionality (Xie et al, 2017).…”
Section: Synthetic Design Of An Elongase Expression Cassette Using Rbmentioning
confidence: 99%
“…We focus on the expression of four enzymes involved in the plantbased VLCFA biosynthesis of A. thaliana using a synthetic polycistronic expression cassette in combination with a selfassembly GFP system. The application of the self-assembly GFP system is a highly innovative method to enable simultaneous solubilization and guided interaction of the plant-derived fatty acid biosynthesis enzyme systems (Cabantous et al, 2005;Cabantous and Waldo, 2006;Venning-Slater et al, 2014;Xie et al, 2017). Furthermore, oleic acid and cerulenin were required to initiate VLCFA biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…These values compared favourably with the previously reported activities of immobilised NanA between 2.5–36 U/mg protein. Moreover, an alternative GFP fusion protein particle approach for immobilisation of NanA resulted in specific NanA activity of 76 mU/mg [51].…”
Section: Performance Of Pha Bead Immobilized Enzymesmentioning
confidence: 99%
“…The direct comparison of specific enzymes immobilised to PHA beads and immobilised to GFP fusion protein particles is particularly relevant because of the similarity in fusion protein construction. In all three cases, NanA, α-amylase, and OpdA the performance under the same reaction conditions is less for the GFP fusion protein particles when compared to the equivalent PHA bead [51]. This is likely to be due to differences in the way the different particles form and the resultant orientation and surface exposure of the respective enzyme.…”
Section: Performance Of Pha Bead Immobilized Enzymesmentioning
confidence: 99%
“…Segami et al , [ 21 ] reported the dynamics of vacuoles and H + -pyrophosphatase visualized by monomeric GFP in Arabidopsis. Several applications of GFP including enzyme immobilization in food processing and biotechnological industries [ 22 ] and screening of multiple membrane proteins in E. coli [ 23 ]. In short, GFP-modified cells were utilized as a biomarker because they can be employed without the need of exogenous substrate.…”
Section: Introductionmentioning
confidence: 99%